The Effect of Acidity Level (pH) and Palm Sugar Sucrose Levels on the Quality of Brown Sugar - Dali, Nasriadi; Chairunnas, Armadi; Amalia, Hilda Ayu Melvi; Puspitasari, Sri Ayu Andini (Universitas Diponegoro, 2024)
Research on the effect of acidity level (pH) and sucrose levels of palm sugar has been successfully carried out. This study aims to determine the effect of acidity level (pH) and sucrose levels of palm sugar on the quality of brown sugar produced. The level of acidity (pH) of palm sugar is set at pH (3, 4, 5, 6, and 7). The quality of brown sugar is divided into three categories, namely quality 1 (high), 2 (moderate), and 3 (low). The sucrose content of palm sugar at pH (3 – 7) was determined by the Luff Schoorl method. The quality of brown sugar was determined organoleptically. The results of determining the sucrose content of palm sugar by Luff Schoorl method at pH (3, 4, 5, 6, and 7) were respectively (11.30, 12.25, 14.17, 15.10 and 16.42%). The results of organoleptic determination of brown sugar quality showed that: (1) palm sugar with sucrose content of 11.30% (pH 3) and 12.25% (pH 4) produced low quality brown sugar; (2) palm sugar with sucrose content of 14.17% (pH 5) and 15.10% (pH 6) produced medium quality brown sugar; (3) palm sugar with a sucrose content of 16.42% (pH 7) produces high quality brown sugar. So, the level of acidity (pH) and sucrose levels of palm sugar affect the quality of brown sugar. The lower the pH and sucrose content of palm sugar, the lower the quality of the brown sugar produced. Conversely, the higher the pH and sucrose content of palm sugar, the higher the quality of the brown sugar produced. Therefore, the quality of palm sugar needs to be maintained so that the pH and sucrose content do not decrease so that the brown sugar produced is of high quality. The results of testing the quality of brown sugar based on SNI-01-3743-1995 show that brown sugar produced from palm sugar at pH 5 – 7 meets SNI requirements. Meanwhile, brown sugar produced from palm sugar at pH 3 and 4 does not meet SNI requirements.